The Nature and Dimensions of Achievement Goals: Mastery, Evaluation, Competition, and Self-Presentation Goals. (28th October 2014) - Lemos, Marina S.; GonÃ§alves, Teresa; Lens, Willy; Rodrigues, LuÃs P.
Abstract The present study aimed to clarify the nature and dimensions of achievement goals and to examine structural differences in studentsâ€™ goals across school levels. Participants were 134 students from 5th and 6th grades, and 423 students from 7th to 9th grades. A variety of achievement goals were assessed, including mastery goals and several performance-related goals representing three main dimensions: competition, self-presentation, and valence. Two alternative models were tested, using confirmatory factor analysis. For middle-school students a three factor model with presentation, competition, and simple evaluation/mastery goals, was found Ï‡Â²(132, N = 134) = 160.9, p < .001; CFI = .94; RMSEA = .04, 95%CI [.02 â€" .06]. In the junior-high sample, one avoidance factor, one competition factor, and a simple evaluation/mastery factor, best fitted the data Ï‡Â²(114, N = 423) = 269.8638 p < .001; CFI = .93; RMSEA = .06, 95%CI [.05 - .07] thus suggesting that distinct dimensions organize younger and older studentsâ€™ motivation. However, common to both grade levels was the existence of (a) separate but low incidence competition goals, and (b) simple evaluation goals, which encompass neither self-presentation nor competition, and are closely linked to mastery goals. Moreover, significant differences were found in the relative importance attached by students to the different types of goals (p < .001 for all comparisons), both at middle-school F(2, 266) = 220.98; p < .001; Î·2 = .624) and at junior-high school F(2, 820) = 464.4; p < .001; Î·2 = .531.